Water electrolysis anode catalyst and preparation method thereof

By using Adams melting reaction and low-temperature in-situ reduction technology to prepare platinum-iridium oxide composite catalysts in the field of water electrolysis, the problem of high ohmic polarization loss of the anode catalyst is solved, more stable catalytic performance and conductivity are achieved, and water electrolysis is promoted Development of technology.

CN119221027APending Publication Date: 2024-12-31SUZHOU HYDROGINE POWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411349974.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the field of water electrolysis, the ohmic polarization loss of anode catalysts is high, which limits the large-scale application of hydrogen production technology, especially in strong oxidation environments, the corrosion resistance and stability of precious metal catalysts are insufficient, resulting in the practical application of non-precious metal catalysts. limited.

Method used

Adams melting reaction is used to prepare platinum-iridium oxide composite catalyst, and the homogeneous combination of iridium nitrate and platinum nitrate is formed by high-temperature melting, and in situ reduction is carried out in low-temperature hydrogen and nitrogen atmosphere to ensure the uniform distribution and activity of platinum and reduce the agglomeration of the catalyst. .

Benefits of technology

The ohmic polarization loss of the water electrolytic anode is significantly reduced, and the stability and conductivity of the catalyst are improved, so that the platinum-iridium oxide composite catalyst can show better performance in water electrolytic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221027A_ABST
    Figure CN119221027A_ABST
Patent Text Reader

Abstract

The invention provides a water electrolysis anode catalyst and a preparation method thereof, and belongs to the technical field of water electrolysis. The preparation method of the water electrolysis anode catalyst comprises the following steps: firstly, carrying out an Asian melting reaction on raw materials including an iridium precursor, a platinum precursor and nitrate to prepare a catalyst precursor, and annealing the catalyst precursor in a hydrogen-containing atmosphere to prepare the water electrolysis anode catalyst. According to the preparation method of the water electrolysis anode catalyst, firstly, raw materials are subjected to an Asian melting reaction, an iridium precursor, a platinum precursor and nitrate are subjected to a high-temperature melting reaction to form iridium nitrate and platinum nitrate, the iridium nitrate and the platinum nitrate are uniformly and tightly combined, then the prepared catalyst precursor is subjected to low-temperature in-situ reduction, and the water electrolysis anode catalyst is obtained. The platinum is uniformly reduced on the periphery of the iridium oxide, and the prepared platinum-iridium oxide composite catalyst is uniform in size, does not agglomerate, and has relatively good activity and relatively good conductivity. The platinum-iridium oxide composite catalyst prepared by the invention can be applied to a water electrolysis anode, and the ohmic polarization loss is obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of water electrolysis, and in particular to a water electrolysis anode catalyst and a preparation method thereof. Background Art

[0002] Electrochemical water splitting using renewable energy sources such as wind, solar, and geothermal energy is an upcoming green hydrogen production technology. Compared with traditional alkaline electrolyzers, proton exchange membrane (PEM) water electrolyzers have the advantages of fast response speed, high power density, high efficiency, and high gas purity, and are considered to be the next generation of hydrogen production technology. Water electrolysis mainly involves two half-reaction processes, the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. The slower kinetics of the oxygen evolution reaction at the anode and the higher overpotential make the research and development of oxygen evolution catalysts an important direction for the large-scale promotion and application of PEM water electrolysis technology.

[0003] At present, the anode catalyst mainly uses metals, metal oxides and alloy catalysts with oxygen evolution ability and corrosion resistance such as Ir, Ru, Pt, Ir oxide, Ru oxide. In a strong oxidizing environment with strong acid Nafion proton conductor and oxygen atoms, non-precious metals such as Ni and Co are easily oxidized or corroded and dissolved. Although there are studies on composite catalysts doped with non-precious metals, there are very few catalysts actually used in large-scale production. Therefore, the current SPE hydroelectric oxygen evolution electrode still uses precious metal catalytic materials.

[0004] Therefore, in the field of water electrolysis, there is still a need to further optimize the anode catalyst so as to obtain a water electrolysis anode having low ohmic polarization loss to meet the needs of actual production. Summary of the invention

[0005] The present application provides a water electrolysis anode catalyst and a preparation method thereof, which has lower ohmic polarization loss.

[0006] The embodiment of the present application is implemented as follows:

[0007] In the first aspect, the present application provides an example method for preparing a water electrolysis anode catalyst, which includes: first subjecting raw materials including an iridium precursor, a platinum precursor and a nitrate to an Adams melt reaction to obtain a catalyst precursor, and annealing the catalyst precursor in an atmosphere containing hydrogen at a temperature of 30°C to 200°C for 30 min to 300 min to obtain a water electrolysis anode catalyst.

[0008] In the above technical scheme, the preparation method of the water electrolysis anode catalyst of the present application first performs an Adams melting reaction on the raw materials, and the iridium precursor, the platinum precursor and the nitrate are melted at high temperature to form iridium nitrate and platinum nitrate, and the iridium nitrate and the platinum nitrate are uniformly and tightly combined, and then the obtained catalyst precursor is reduced in situ at low temperature to make the platinum uniformly reduced around the iridium oxide, and the obtained platinum-iridium oxide composite catalyst has uniform size, basically no agglomeration, and takes into account better activity and better conductivity. The platinum-iridium oxide composite catalyst prepared in the present application can be applied to the water electrolysis anode and significantly reduce the ohmic polarization loss.

[0009] In some possible implementation schemes, the atmosphere is a mixture of hydrogen and nitrogen; optionally, the volume ratio of hydrogen to nitrogen is 1:4 to 1:16.

[0010] In the above technical scheme, the preparation method of the water electrolysis anode catalyst of the present application adopts low-temperature hydrogen and nitrogen in-situ reduction of the catalyst precursor to obtain a platinum-iridium oxide composite catalyst, and when the volume ratio of hydrogen and nitrogen is within the above range, the platinum can be reduced so that the platinum is evenly reduced around the iridium oxide.

[0011] In some possible embodiments, the annealing temperature is 50°C to 100°C.

[0012] In some possible embodiments, the iridium precursor includes at least one of chloroiridic acid, iridium trichloride, iridium tetrachloride, potassium iridium chloroate hydrate, sodium iridium chloroate hydrate, iridium nitrate and tetrairidium dodecacarbonyl, and / or the platinum precursor includes at least one of chloroplatinic acid, platinum tetrachloride and potassium chloroplatinate.

[0013] In some possible implementation schemes, the molar ratio of the platinum element in the platinum precursor to the iridium element in the iridium precursor is 1:3 to 1:16.

[0014] In the above technical solution, by controlling the molar ratio of the platinum element in the platinum precursor and the iridium element in the iridium precursor within the above range, platinum can be uniformly reduced around the iridium oxide, and the catalytic performance of the obtained platinum-iridium oxide composite catalyst is stable.

[0015] In some possible implementation schemes, the sum of the molar amount of the iridium element in the iridium precursor and the molar amount of the platinum element in the platinum precursor is x, the molar amount of the nitrate is y, and x:y=1:10-100.

[0016] In some possible embodiments, the temperature of the Adams melt reaction is 300° C. to 800° C., and the time is 10 min to 120 min.

[0017] In the above technical solution, by controlling the temperature and time of the Adams melt reaction, it is beneficial to make the iridium precursor, platinum precursor and nitrate undergo a high-temperature melt reaction to form iridium nitrate and platinum nitrate, and the iridium nitrate and platinum nitrate are uniformly and tightly combined.

[0018] In some possible implementation schemes, before subjecting the raw materials to the Adams melt reaction, the raw materials are first ball-milled and dried to obtain a mixed powder.

[0019] In the above technical solution, the ball milling treatment method can fully disperse and evenly mix the iridium precursor, platinum precursor and nitrate, which is convenient for evenly mixing platinum oxide and iridium oxide in post-treatment, and effectively enhances electronic conduction and electrical conductivity.

[0020] In some possible implementation schemes, the rotation speed of the ball mill is 450 r / min to 650 r / min, and the ball milling time is 6 h to 18 h.

[0021] In a second aspect, the present application provides an anode catalyst for water electrolysis, which is prepared according to the method for preparing the anode catalyst for water electrolysis in the above embodiment.

[0022] In the above technical solution, the water electrolysis anode catalyst of the present application can be applied to the water electrolysis anode and significantly reduce the ohmic polarization loss. Moreover, the water electrolysis anode catalyst can be applied to systems with or without a carrier. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 The XRD diagrams of the anode catalysts for water electrolysis of Examples 1 to 3 and Comparative Example 1 of the present application;

[0025] Figure 2 XRD diagrams of the anode catalysts for water electrolysis of Examples 4 to 5 and Comparative Example 1 of the present application;

[0026] Figure 3 This is the XRD pattern of the anode catalyst for water electrolysis of Example 6 of the present application;

[0027] Figure 4 Polarization curves of anode catalysts for water electrolysis of Examples 1 to 6 of the present application;

[0028] Figure 5It is a polarization curve diagram of the water electrolysis anode catalyst of Examples 7 to 9 of the present application and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0029] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0030] The present application found that adding Pt to the anode OER catalyst of water electrolysis can improve the conductivity. The platinum-iridium oxide composite catalyst can be prepared by high-temperature thermal decomposition and liquid phase reduction. However, the platinum-iridium oxide composite catalyst obtained by high-temperature thermal decomposition is relatively agglomerated, which is not conducive to the exposure of active sites. The platinum particles loaded with iridium oxide obtained by liquid phase reduction have weak mutual binding force, which easily causes platinum agglomeration and catalyst deactivation during the reaction process. The performance of the commercially available platinum black loaded iridium oxide catalyst is unstable, mainly because of its uneven distribution of platinum.

[0031] Based on this, the present application provides a method for preparing a water electrolysis anode catalyst, which comprises the following steps:

[0032] S1. Preparation of mixed powder

[0033] The raw materials including an iridium precursor, a platinum precursor, a nitrate and a solvent are mixed and dried to obtain a mixed powder.

[0034] The iridium precursor includes at least one of chloroiridic acid, iridium trichloride, iridium tetrachloride, potassium iridium chloroate hydrate, sodium iridium chloroate hydrate, iridium nitrate and tetrairidium dodecacarbonyl.

[0035] The platinum precursor includes at least one of chloroplatinic acid, platinum tetrachloride and potassium chloroplatinate.

[0036] Optionally, the molar ratio of the platinum element in the platinum precursor to the iridium element in the iridium precursor is 1:3 to 1:16.

[0037] As an example, the molar ratio of the platinum element in the platinum precursor to the iridium element in the iridium precursor can be any value of 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15 and 1:16 or between any two values.

[0038] By controlling the molar ratio of the platinum element in the platinum precursor to the iridium element in the iridium precursor within the above range, platinum can be uniformly reduced around the iridium oxide, and the catalytic performance of the prepared platinum-iridium oxide composite catalyst is stable.

[0039] Nitrates include sodium nitrate.

[0040] Optionally, the ratio of the sum of the molar amount of the iridium element in the iridium precursor and the molar amount of the platinum element in the platinum precursor to the molar amount of the nitrate is 1:10-100.

[0041] In other words, the sum of the molar amount of the iridium element in the iridium precursor and the molar amount of the platinum element in the platinum precursor is x, the molar amount of the nitrate is y, and x:y=1:10-100.

[0042] As an example, the ratio of the sum of the molar amount of iridium element in the iridium precursor, the molar amount of platinum element in the platinum precursor, and the molar amount of nitrate can be any value of 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90 and 1:100 or between any two values.

[0043] The solvent includes at least one of isopropanol, ethanol, methanol and water, and the above solvent does not introduce impurities.

[0044] It should be noted that the iridium precursor, the platinum precursor, the nitrate and the solvent can be mixed at the same time, or the iridium precursor and the platinum precursor can be dispersed in the solvent first, and then the nitrate is added to the mixture including the iridium precursor, the platinum precursor and the solvent. The order of addition during the mixing process can be selected according to actual needs, and is not limited here.

[0045] Optionally, the method of mixing the raw materials includes ball milling, which can be performed in a planetary ball mill.

[0046] The speed of the ball mill of the planetary ball mill is 450r / min to 650r / min, the ball milling time is 6h to 18h, and the ball milling direction is turned every 30min to 50min during the ball milling process. It can be understood that the speed of the ball mill refers to the final speed of the ball mill after the revolution speed of the main wheel and the rotation speed of the ball mill are superimposed.

[0047] As an example, the rotation speed of the ball mill of the planetary ball mill can be any value of 450r / min, 480r / min, 500r / min, 520r / min, 550r / min, 580r / min, 600r / min, 620r / min and 650r / min or between any two values.

[0048] The ball milling treatment method can fully disperse and evenly mix the iridium precursor, platinum precursor and nitrate, making it easier to evenly mix the platinum oxide and iridium oxide in post-processing, effectively enhancing electronic conduction and electrical conductivity.

[0049] Optionally, the drying temperature is 60°C-90°C.

[0050] By keeping the drying temperature within the above range, the mixed powder can be quickly dried to obtain the mixed powder. In order to avoid the introduction of impurities, the drying can be carried out in a vacuum drying device.

[0051] S2, Adams melt reaction

[0052] The prepared mixed powder is heat-treated at a temperature of 300° C. to 800° C. for 10 min to 120 min to prepare a catalyst precursor.

[0053] As an example, the temperature of the heat treatment can be any value among 300°C, 400°C, 500°C, 600°C, 700°C and 800°C or between any two values, and the time of the heat treatment can be any value among 10min, 30min, 60min, 90min, 100min and 120min or between any two values.

[0054] By controlling the temperature and time of the Adams melt reaction, it is beneficial to make the iridium precursor, the platinum precursor and the nitrate undergo a high-temperature melt reaction to form iridium nitrate and platinum nitrate, and the iridium nitrate and platinum nitrate are uniformly and tightly combined.

[0055] Optionally, in order to avoid the introduction of impurities, after the mixed powder is heat-treated, the product obtained after the heat treatment is washed with deionized water, and then positive pressure filtered, and the obtained filter residue is dried in a vacuum drying oven for 6h to 12h to obtain a catalyst precursor.

[0056] S3, reduction reaction

[0057] The catalyst precursor is annealed in an atmosphere containing hydrogen at a temperature of 30° C. to 200° C. for 30 min to 300 min to obtain a water electrolysis anode catalyst.

[0058] As an example, the annealing temperature can be any value among 30°C, 50°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C and 200°C or between any two values, and the annealing time can be any value among 30min, 60min, 90min, 120min, 150min, 180min, 210min, 240min, 270min and 300min or between any two values.

[0059] Optionally, the annealing temperature is 50°C to 100°C.

[0060] If the annealing temperature is too low, platinum oxide cannot be effectively reduced. If the annealing temperature is too high, iridium oxide will be reduced and the catalyst will agglomerate, affecting the activity of the catalyst and the conductivity in the membrane electrode.

[0061] Optionally, the atmosphere is a mixture of hydrogen and nitrogen.

[0062] Optionally, the volume ratio of hydrogen to nitrogen is 1:4 to 1:16.

[0063] As an example, the volume ratio of hydrogen to nitrogen may be any value of 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, and 1:16 or between any two values.

[0064] When the volume ratio of hydrogen to nitrogen is within the above range, platinum can be reduced so that platinum is uniformly reduced around iridium oxide.

[0065] The preparation method of the water electrolysis anode catalyst of the present application first subjects the raw materials to an Adams melt reaction, and the iridium precursor, the platinum precursor and the nitrate are subjected to a high-temperature melt reaction to form iridium nitrate and platinum nitrate, and the iridium nitrate and the platinum nitrate are uniformly and tightly combined, and then the obtained catalyst precursor is subjected to low-temperature in-situ reduction, so that the platinum is uniformly reduced around the iridium oxide, and the obtained platinum-iridium oxide composite catalyst has uniform size, is basically not agglomerated, and has both good activity and good conductivity. The platinum-iridium oxide composite catalyst prepared in the present application can be applied to the water electrolysis anode, and significantly reduces the ohmic polarization loss. And this water electrolysis anode catalyst can be applicable to systems with or without a carrier.

[0066] The present application also provides a water electrolysis anode catalyst, which is prepared according to the preparation method of the water electrolysis anode catalyst in the above embodiment.

[0067] The following is a further detailed description of a water electrolysis anode catalyst and a preparation method thereof of the present application in conjunction with embodiments.

[0068] Example 1

[0069] The present invention provides a water electrolysis anode catalyst and a preparation method thereof, which comprises the following steps:

[0070] S1. Preparation of mixed powder

[0071] Weigh 0.236g of chloroplatinic acid aqueous solution and 1.029g of chloroiridic acid aqueous solution and disperse them in isopropanol to prepare a mixture, the molar ratio of platinum element to iridium element is 1:4, and place the mixture in the ball mill of a planetary ball mill, and then weigh 9.926g of sodium nitrate and place it in the ball mill of the planetary ball mill, and mix them for 10 hours by ball milling, during which the speed of the ball mill is 600r / min, and the direction is reversed every 45min. After the mixing is completed, dry it in a vacuum drying oven at 80°C until the weight no longer changes, and obtain a mixed powder.

[0072] S2, Adams melt reaction

[0073] The obtained mixed powder was placed in a crucible, and the crucible was placed in a 500°C muffle furnace for Adams melting reaction, and then cooled to room temperature with the furnace after keeping the temperature for 30 minutes. The product obtained after the heat treatment was then washed with deionized water, and then positive pressure filtered, and the obtained filter residue was dried in a vacuum drying oven for 10 hours to obtain a catalyst precursor, which was recorded as PtO2 / IrO2.

[0074] S3, reduction reaction

[0075] PtO2 / IrO2 was placed in a porcelain boat and annealed at 75°C for 2 hours in a mixed atmosphere of hydrogen and nitrogen with a volume ratio of 1:8 to obtain a platinum-iridium oxide composite catalyst, recorded as Pt / IrO2 catalyst.

[0076] Example 2

[0077] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. Embodiment 2 changes the annealing temperature in step S3 to 50° C. on the basis of Embodiment 1, while other aspects remain unchanged.

[0078] Example 3

[0079] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. Embodiment 3 is based on Embodiment 1, except that the annealing temperature in step S3 is changed to 100° C., while other aspects remain unchanged.

[0080] Example 4

[0081] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. Embodiment 4 changes the volume ratio of hydrogen and nitrogen in step 3 of Embodiment 1 to 1:16, while other aspects remain unchanged.

[0082] Example 5

[0083] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. Embodiment 5 is based on Embodiment 1, wherein the volume ratio of hydrogen to nitrogen in step S3 is changed to 1:4, while other aspects remain unchanged.

[0084] Example 6

[0085] The present application provides a water electrolysis anode catalyst and a preparation method thereof. In Example 6, based on Example 1, commercially available titanium dioxide oxide is added during the ball milling process in step S1, and the addition ratio is n Pt :n Ir :n TiO2 =1:4:9.6, other factors remain unchanged.

[0086] Example 7

[0087] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. In Embodiment 7, based on Embodiment 1, the molar ratio of platinum element to iridium element in step S1 is changed to 1:3, while other aspects remain unchanged.

[0088] Example 8

[0089] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. Embodiment 8 changes the molar ratio of platinum element to iridium element in step S1 to 1:5 on the basis of Embodiment 1, while other aspects remain unchanged.

[0090] Example 9

[0091] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. Embodiment 9 changes the molar ratio of platinum element to iridium element in step S1 to 1:6 based on Embodiment 1, while other aspects remain unchanged.

[0092] Example 10

[0093] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. Embodiment 10 changes the annealing time in step S3 to 0.5 h on the basis of Embodiment 1, while other aspects remain unchanged.

[0094] Embodiment 11

[0095] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. Embodiment 11 changes the annealing time in step S3 to 1 hour on the basis of Embodiment 1, while other aspects remain unchanged.

[0096] Example 12

[0097] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. Embodiment 12 changes the annealing time in step S3 to 3 hours on the basis of Embodiment 1, while other aspects remain unchanged.

[0098] Example 13

[0099] The embodiments of the present application provide a water electrolysis anode catalyst and a preparation method thereof. Embodiment 13 changes the annealing time in step S3 to 5 hours on the basis of Embodiment 1, while other aspects remain unchanged.

[0100] Comparative Example 1

[0101] The comparative example of the present application provides a water electrolysis anode catalyst and a preparation method thereof, which comprises the following steps:

[0102] S1. Preparation of mixed powder

[0103] Weigh 0.236g of chloroplatinic acid aqueous solution and 1.029g of chloroiridic acid aqueous solution and disperse them in isopropanol to prepare a mixture, the molar ratio of platinum element to iridium element is 1:4, and place the mixture in the ball mill of a planetary ball mill, and then weigh 9.926g of sodium nitrate and place it in the ball mill of the planetary ball mill, and mix them for 10 hours by ball milling, during which the speed of the ball mill is 600r / min, and the direction is reversed every 45min. After the mixing is completed, dry it in a vacuum drying oven at 80°C until the weight no longer changes, and obtain a mixed powder.

[0104] S2, Adams melt reaction

[0105] The obtained mixed powder was placed in a crucible, and the crucible was placed in a 500°C muffle furnace for Adams melting reaction, and then cooled to room temperature with the furnace after keeping the temperature for 30 minutes. The product obtained after the heat treatment was then washed with deionized water, and then positive pressure filtered, and the obtained filter residue was dried in a vacuum drying oven for 10 hours to obtain a catalyst.

[0106] Comparative Example 2

[0107] The comparative example of the present application provides a water electrolysis anode catalyst and a preparation method thereof, which comprises the following steps:

[0108] S1. Preparation of mixed powder

[0109] Weigh 0.09g of commercially available platinum black and 1.029g of chloroiridic acid aqueous solution and disperse them in isopropanol to prepare a mixture, the molar ratio of platinum element to iridium element is 1:4, and place the mixture in the ball mill of a planetary ball mill, and then weigh 9.926g of sodium nitrate and place it in the ball mill of the planetary ball mill, and mix them for 10h by ball milling, during which the speed of the ball mill is 600r / min, and the direction is reversed every 45min. After the mixing is completed, dry it in a vacuum drying oven at 80°C until the weight no longer changes, and obtain a mixed powder.

[0110] S2, Adams melt reaction

[0111] The obtained mixed powder was placed in a crucible, and the crucible was placed in a 500°C muffle furnace for Adams melting reaction, and then cooled to room temperature with the furnace after keeping the temperature for 30 minutes. The product obtained after the heat treatment was then washed with deionized water, and then positive pressure filtered, and the obtained filter residue was dried in a vacuum drying oven for 10 hours to obtain a catalyst.

[0112] Comparative Example 3

[0113] The comparative example of the present application provides a water electrolysis anode catalyst and a preparation method thereof, which comprises the following steps:

[0114] S1. Preparation of mixed powder

[0115] 1.029g of chloroiridic acid aqueous solution was weighed and dispersed in isopropanol to prepare a mixture, and the mixture was placed in a ball mill of a planetary ball mill, and 9.926g of sodium nitrate was weighed and placed in the ball mill of the planetary ball mill, and mixed by ball milling for 10 hours, during which the speed of the ball mill was 600r / min, and the direction was reversed every 45 minutes. After the mixing was completed, it was dried in a vacuum drying oven at 80°C until the weight no longer changed, and a mixed powder was obtained.

[0116] S2, Adams melt reaction

[0117] The obtained mixed powder was placed in a crucible, and the crucible was placed in a 500°C muffle furnace for Adams melting reaction, and then cooled to room temperature with the furnace after keeping the temperature for 30 minutes. The product obtained after the heat treatment was then washed with deionized water, and then positive pressure filtered, and the obtained filter residue was dried in a vacuum drying oven for 10 hours to obtain a catalyst.

[0118] The parameters of the reduction reactions of Examples 1 to 13 and Comparative Examples 1 to 3 are shown in Table 1.

[0119] Table 1 Parameters of the reduction reaction of Examples 1 to 13 and Comparative Examples 1 to 3

[0120]

[0121] Test Example 1

[0122] The XRD patterns of the catalysts prepared in Examples 1 to 6 and Comparative Example 1 were measured respectively. Figures 1 to 3 shown.

[0123] Depend on Figure 1 It can be seen that Examples 1 to 3 all reduced platinum through reduction reactions, wherein Example 1 reduced platinum normally, Example 2 had a lower annealing temperature and a lower degree of platinum reduction, and Example 3 had a higher annealing temperature and reduced both platinum and iridium. Comparative Example 1 had no reduction reaction and did not reduce platinum.

[0124] Depend on Figure 2 It can be seen that Examples 1 and 4 to 5 all reduce platinum through reduction reactions, wherein Example 1 reduces platinum normally, Example 4 has a lower hydrogen content in the annealing atmosphere and a lower degree of platinum reduction, and Example 5 has a higher hydrogen content in the annealing atmosphere and reduces both platinum and iridium.

[0125] Depend on Figure 3 It can be seen that in Example 6, platinum is reduced through the reduction reaction.

[0126] Test Example 2

[0127] The catalyst membrane electrode performance test was carried out on the catalysts prepared in Examples 1 to 13 and Comparative Examples 1 to 3. The results are as follows: Figures 4-5 As shown in Tables 2-3.

[0128] The test method is as follows:

[0129]

Preparation of anode catalyst slurry

[0130] Isopropanol and water were mixed at a volume ratio of 5:2, and 0.5 g of the catalyst obtained in each example and comparative example was added to obtain a catalyst slurry with a solid content of 15%.

[0131] Preparation of CCM

[0132] Each anode catalyst slurry is sprayed on the surface of the PTFE membrane to form an anode catalyst layer, and then transferred to the Nafion115 proton exchange membrane together with the cathode Pt / C catalyst layer coated on the PTFE membrane, and thermally transferred to form a CCM.

[0133]

Membrane electrode activation and testing

[0134] The prepared CCM was packaged with the titanium felt PTL as the anode and the carbon paper GDL as the cathode to form an electrolytic cell. In constant current mode, the current was scanned from 0.01 A / cm 2 Up to 4A / cm 2 , record the current and voltage values, and obtain the polarization curve, such as Figures 3-4 The analytical values ​​of the polarization curves are shown in 2 to 4, where η ohmic is the ohmic polarization loss, η OER is the catalyst activity polarization loss, η mt Transmission polarization loss.

[0135] Take the current density in the polarization curve as 1A / cm 2 , 2A / cm 2 、3A / cm 2 4A / cm 2 The ohmic polarization loss (η ohmic ), catalyst activity polarization loss (η OER ) and transmission polarization loss (η mt ), and the results are shown in Tables 2 to 3.

[0136] Table 2 Polarization curves of Examples 1 to 13 and Comparative Examples 1 to 3 with a current density of 1 A / cm 2 and 2A / cm 2 The parsed value of

[0137]

[0138] Table 3 Polarization curves of Examples 1 to 13 and Comparative Examples 1 to 3 with a current density of 3 A / cm 2 and 4A / cm2 The parsed value of

[0139]

[0140]

[0141] It can be seen from Examples 1 to 13 that the water electrolysis anode catalyst prepared by the preparation method of the present application has lower ohmic polarization loss, catalyst activity polarization loss and transport polarization loss.

[0142] From the comparison between Example 1 and Comparative Example 1, it can be seen that Comparative Example 1 does not have a reduction step, and the CCM membrane electrode prepared by the water electrolysis anode catalyst has a current density of 4A / cm 2 The ohmic polarization loss is 0.3210, the catalyst activity polarization loss is 0.3574, and the transport polarization loss is 0.1133, all of which are higher than those of the water electrolysis anode catalyst in Example 1. 2 Ohmic polarization loss, catalyst activity polarization loss and transport polarization loss.

[0143] From the comparison between Example 1 and Comparative Examples 2-a and 2-b (Comparative Examples 2-a and 2-b are parallel samples of Comparative Example 2), it can be seen that both Comparative Examples 2-a and 2-b use commercially available platinum black to replace the platinum precursor. Since the distribution of commercially available platinum black is uncontrollable, there is a large difference between the data of Comparative Examples 2-a and Comparative Examples 2-b. Among them, the CCM membrane electrode prepared by the water electrolysis anode catalyst of Comparative Example 2-a has a current density of 4A / cm 2 The ohmic polarization loss is 0.2631, the catalyst activity polarization loss is 0.3423, and the transport polarization loss is 0.1372, all of which are higher than the CCM membrane electrode prepared by the water electrolysis anode catalyst in Example 1 at a current density of 4A / cm 2 The ohmic polarization loss, catalyst activity polarization loss and transport polarization loss of Comparative Example 2-b were obtained by using the CCM membrane electrode prepared from the water electrolysis anode catalyst at a current density of 4A / cm 2 The ohmic polarization loss is 0.2391, the catalyst activity polarization loss is 0.3417, and the transport polarization loss is 0.1291, all of which are higher than the CCM membrane electrode prepared by the water electrolysis anode catalyst in Example 1 at a current density of 4A / cm 2 The ohmic polarization loss, catalyst activity polarization loss and transport polarization loss of Comparative Example 2-b showed that the CCM membrane electrode prepared by the water electrolysis anode catalyst at a current density of 4A / cm 2 The ohmic polarization loss, catalyst activity polarization loss and transport polarization loss are all lower than those of the water electrolysis anode catalyst of Comparative Example 2-a. The CCM membrane electrode prepared at a current density of 4A / cm 2The ohmic polarization loss, catalyst activity polarization loss and transport polarization loss are shown in Table 2, which indicates that the commercially available platinum black in Comparative Example 2-a is unevenly distributed, while the commercially available platinum black in Comparative Example 2-b is evenly distributed.

[0144] From the comparison between Example 1 and Comparative Example 3, it can be seen that the CCM membrane electrode prepared by the water electrolysis anode catalyst in Comparative Example 3 without platinum precursor has a current density of 4A / cm 2 The ohmic polarization loss is 0.3099, and the catalyst active polarization loss is 0.3566, both of which are higher than the CCM membrane electrode prepared by the water electrolysis anode catalyst in Example 1 at a current density of 4A / cm 2 Ohmic polarization loss and catalyst activity polarization loss.

[0145] The above description is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a water electrolysis anode catalyst, characterized in that: The preparation method of the water electrolysis anode catalyst comprises: firstly subjecting raw materials including an iridium precursor, a platinum precursor and a nitrate to an Adams melt reaction to obtain a catalyst precursor, and annealing the catalyst precursor in an atmosphere containing hydrogen at a temperature of 30° C. to 200° C. for 30 min to 300 min to obtain a water electrolysis anode catalyst.

2. The method for preparing a water electrolysis anode catalyst according to claim 1, characterized in that: The atmosphere is a mixture of hydrogen and nitrogen; Optionally, the volume ratio of the hydrogen to the nitrogen is 1:4 to 1:

16.

3. The method for preparing a water electrolysis anode catalyst according to claim 1, characterized in that: The annealing temperature is 50°C to 100°C.

4. The method for preparing a water electrolysis anode catalyst according to claim 1, characterized in that: The iridium precursor comprises at least one of chloroiridic acid, iridium trichloride, iridium tetrachloride, potassium iridium chloroate hydrate, sodium iridium chloroate hydrate, iridium nitrate and tetrairidium dodecacarbonyl, and / or The platinum precursor includes at least one of chloroplatinic acid, platinum tetrachloride and potassium chloroplatinate.

5. The method for preparing a water electrolysis anode catalyst according to claim 1, characterized in that: The molar ratio of the platinum element in the platinum precursor to the iridium element in the iridium precursor is 1:3 to 1:

16.

6. The method for preparing a water electrolysis anode catalyst according to claim 1, characterized in that: The sum of the molar amount of the iridium element in the iridium precursor and the molar amount of the platinum element in the platinum precursor is x, the molar amount of the nitrate is y, and x:y=1:10-100.

7. The method for preparing a water electrolysis anode catalyst according to claim 1, characterized in that: The temperature of the Adams melt reaction is 300° C. to 800° C., and the time is 10 min to 120 min.

8. The method for preparing a water electrolysis anode catalyst according to claim 1, characterized in that: Before subjecting the raw materials to the Adams melt reaction, the raw materials are firstly ball-milled and dried to obtain a mixed powder.

9. The method for preparing a water electrolysis anode catalyst according to claim 8, characterized in that: The rotation speed of the ball mill is 450 r / min to 650 r / min, and the ball milling time is 6 h to 18 h.

10. A water electrolysis anode catalyst, characterized in that: The water electrolysis anode catalyst is prepared according to the method for preparing the water electrolysis anode catalyst according to any one of claims 1 to 9.